Cue-based treatment for light smokers: A proof of concept pilot. (March 2021) - Pollak, Kathryn I.; Oliver, Jason A.; Pieper, Carl; Davis, James M.; Gao, Xiaomei; Noonan, Devon; Kennedy, Danielle; Granados, Isa; Fish, Laura J.
Highlights: Light smoking significantly increases the risk of all-cause mortality. Light smoking appears to be driven by conditioned cues and nicotine delivery. Cue-based treatment can be integrated into the real world through text messaging systems. Cue-based treatment was feasible and accepted among light smokers. Abstract: Introduction: Light smoking (smoking ≤ 10 cigarettes per day or on some days) has become increasingly prevalent in the US and increases morbidity and mortality. Many light smokers do not experience significant nicotine withdrawal but instead smoke in response to cues. Minimal evidence exists supporting interventions to help light smokers quit smoking. Methods: We present results from a proof-of-concept pilot study designed to evaluate the feasibility and acceptability of a cue-based smoking cessation intervention targeted to light daily and intermittent smokers. Participants were randomized to one of two arms: Arm 1) standard smoking cessation treatment or Arm 2) standard smoking cessation treatment + enhanced cue-based treatment that included interactive texting to extend cue exposure treatment to real-world settings and cue management counseling. Outcomes included feasibility (number of participants who were recruited and who completed the intervention), acceptability (intervention ratings), and preliminary efficacy (7-day point prevalence abstinence). Results: We randomized 24 English and Spanish-speaking light smokers, 13 to the treatment arm and 11 to the control arm. Across both arms, 77% attended all counseling sessions, 90% rated these sessions as very useful and 100% said that they would recommend the intervention to a friend. 15% in the treatment arm had biochemically-validated smoking abstinence compared to 0% in the standard counseling arm. Conclusions: Results from this proof-of-concept study demonstrated that a cue-based intervention is feasible and acceptable among light smokers and suggests the need for a fully powered study to assess this approach. Trial registration: This study is registered at www.clinicaltrials.gov NCT03416621.